The Public Sphere and Online, Independent Journalism - Beers, David (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
The rapid evolution of online, independent journalism affords educators an opportunity to increase students’ understanding of the nature and power of the news media. Drawing from Habermas’s theories of the role of the public sphere in democratic discourse, the author, as founder of an online news publication, traces trends in concentrated corporate ownership of Canadian media, new forms of online journalism and their democratic potential and limitations, and ways in which educators can help students deconstruct and participate in traditional and newer forms of news media. Key words: media democracy, Habermas, Internet, blogosphere, citizenship L’évolution rapide du journalisme indépendant en ligne fournit aux enseignants une occasion de mieux faire comprendre aux élèves la nature et le pouvoir des médias d’information. S’inspirant des théories de Habermas sur le rôle de la sphère publique dans le discours démocratique, l’auteur, qui a créé un bulletin en ligne, retrace les tendances quant à la concentration des médias au Canada, les nouvelles formes de journalisme en ligne, leur potentiel et leurs limites pour la démocratie ainsi que les façons dont les éducateurs peuvent aider les élèves à développer un esprit critique et à utiliser les médias, traditionnels ou nouveaux. Mots clés : médias, démocratie, Habermas, Internet, blogosphère, conscience citoyenne.